Diffusion tensor imaging of the inferior alveolar nerve using 3T MRI: a study for quantitative evaluation and fibre tracking - Kotaki, Shinya (Dentomaxillofac Radiol, 2016)
OBJECTIVES: Diffusion tensor imaging (DTI) can provide structural information and objective values for nerves. The aims of this study were to perform quantitative evaluation and fibre tracking of the normal inferior alveolar nerve (IAN) using DTI on 3.0-T MRI. METHODS: DTI was applied to 92 IANs of 46 healthy volunteers. Circular regions of interest (ROIs) were placed on three different positions at the mandibular foramen, second molar and mental foramen of each nerve on apparent diffusion coefficient (ADC) and fractional anisotropy (FA) maps, and the ADC and FA of each ROI were measured. Differences in the values arising from the nerve positions were evaluated. Furthermore, fibre tracking of the IANs was performed by tractography, and the quality of visualization was evaluated. RESULTS: There were no significant differences in the ADC and FA between the right and left sides regardless of the anteroposterior positions. Regarding differences arising from the anteroposterior measurement positions, the ADC and FA showed no significant differences (p > 0.017), except for the ADCs between the positions at the mandibular foramen and mental foramen in the left side (p = 0.0068). Overall, 70 (76%) of the 92 IANs could be visualized fully or partially by tractography. CONCLUSIONS: The ADC and FA of the IAN were successfully obtained from healthy volunteers using DTI and were confirmed to be symmetrical regardless of the measurement positions. DTI is a feasible technique for the quantitative evaluation and visualization of the IAN.